Analisis Ketahanan Pangan Wilayah di Kecamatan Bungku Tengah Kabupaten Morowali - Hasmiati; Sitti Rahma Ma'mun; Bambang Indro Yuwono (Agrisurya, 2022)
Food availability is very important in determining the food security of a region. However, the availability of food alone is not enough to determine the level of food security. This study aimed to measure the level of regional food security by using a composite index. This research was conducted in Bungku Tengah subdistrict from April to May 2014. This study used secondary data from the Central Statistics Agency (BPS) and the Food Agency of Morowali Regency, as well as field observations. The observed data includes three aspects, namely food production, distribution and consumption aspects. The data analysis technique used in this research is the food access analysis guide from the Food Security Agency in 2008. The results shows that the composite index of the three aspects of food security is quite high. Aspects of distribution, education and the availability of market facilities contribute to the combined value. However, if viewed from the aspect of availability, local production is still in deficit and income levels are classified as low so that it has the potential to cause food insecurity in the area. Programs to increase the planted area and intensification need to be pursued to increase production. Likewise, is needed food diversification to reduce dependence on rice.